Is there cross-species transmission to pigs of Avian Influenza virus within poultry farms with previous outbreak of avian influenza : No cross-species transmission to pigs of Avian Influenza virus (African Journal of Biomedical Research, 2021)
Interspecies interaction between pigs and poultry has not been well elucidated in Ghana. Although avian influenza circulated in some small commercial holdings with mixed poultry-pig system in the Greater Accra Region of Ghana, the investigation on possible cross transmission from poultry to pigs has not been elucidated. To this end, 350 blood and nasal swab respectively from pigs were screened for influenza A by Real Time RT-PCR and enzyme-linked immunosorbent assay (ELISA). There was no evidence of avian influenza in pigs within the poultry farms. However, biosecurity compliance among the farmers was suboptimal, suggesting possible cross transmission in the future as pig population density continues to increase. Therefore, active surveillance in those farms should be strengthened for unpredictable future pandemic.
Keywords: Avian influenza virus, pigs, chicken, cross species, transmission